2013
DOI: 10.1371/journal.pone.0054431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parenteral Selenium Supplementation in Critically Ill Patients: A Systematic Review and Meta-Analysis

Abstract: BackgroundIt is currently unclear whether parenteral selenium supplementation should be recommended in the management of critically ill patients. Here we conducted a systematic review and meta-analysis to assess the efficacy of parenteral selenium supplementation on clinical outcomes.Methods/Principal FindingsRandomized trials investigating parenteral selenium supplementation administered in addition to standard of care to critically ill patients were included. CENTRAL, Medline, EMBASE, the Science Citation In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 43 publications
2
50
3
4
Order By: Relevance
“…These attempts have had some success in restoring mitochondrial and organ function, reducing inflammatory signaling, and reducing oxidative stress (10,(63)(64)(65). Current therapies for septic patients that are critically ill include supplementation with antioxidants and have proven to help reduce the mortality rate of these patients (66)(67)(68). To the best of our knowledge, we are the first to use mitochondrion-targeted antioxidants in vivo as a method for improving the innate immune response to infection.…”
Section: Discussionmentioning
confidence: 99%
“…These attempts have had some success in restoring mitochondrial and organ function, reducing inflammatory signaling, and reducing oxidative stress (10,(63)(64)(65). Current therapies for septic patients that are critically ill include supplementation with antioxidants and have proven to help reduce the mortality rate of these patients (66)(67)(68). To the best of our knowledge, we are the first to use mitochondrion-targeted antioxidants in vivo as a method for improving the innate immune response to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that selenium replacement in critically ill patients is beneficial in reducing infections (such as ventilator acquired pneumonia) and mortality [32,33]. This led us to investigate the impact of ECMO on plasma selenium levels.…”
Section: Discussionmentioning
confidence: 99%
“…A recent, large, blinded RCT failed to demonstrate benefit from antioxidant combination, including selenium supplementation. However, the dose of selenium used was relatively low, and studies demonstrating benefit from selenium investigated cocktails containing selenium at higher doses (52)(53)(54). Use of probiotics has shown benefit in the ICU setting when commercially available products are provided, reducing ventilator-associated pneumonia, likelihood to acquire antibioticassociated diarrhea, pseudomembranous colitis, and possibly overall infections (55)(56)(57).…”
Section: Formula Selectionmentioning
confidence: 99%